Recent concepts in biodegradable polymers for tissue engineering paradigms: a critical review. (17th February 2019) - Iqbal, Naseer; Khan, Abdul Samad; Asif, Anila; Yar, Muhammad; Haycock, John W.; Rehman, Ihtesham Ur
ABSTRACT: Tissue engineering and regenerative medicine are emerging as future approaches for the treatment of acute and chronic diseases. Numerous clinical conditions exist today and include congenital disorders, trauma, infection, inflammation, and cancer, in which hard and soft tissue damage, organ failure and loss are still not treated effectively. Researchers are constantly developing new biomaterials and tissue-engineered technologies to stimulate tissue regeneration. Various emerging approaches according to organ, tissue, disease and disorder are identified. Irrespective, engineered biomaterials are required to regenerate and ultimately reproduce the original physiological, biological, chemical, and mechanical properties. Biodegradable materials have been used extensively as regenerative therapies. The selection, design, biological and physicochemical properties of these materials are important and must be considered for stimulating tissue growth. In this review, we critique recently developed biodegradable materials for tissue regeneration of some targeted organs e.g., skin, nerves, blood vessels, heart, cornea, trachea, dental/oral structure and bones.